Coastal parents Perceptions of the Implementation of Early Childhood Education in Buton Islands - La Jeti Jeti; Manan Manan (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The purpose of this study was to obtain information on understanding of early childhood education in coastal communities in the Buton Islands. This research uses descriptive qualitative research. The subjects in this study were teachers, and parents in the coastal district of Buton.  Based on the results of the study, the coastal communities in the Buton Islands do not yet fully have knowledge about the nature of early childhood development.  Based on the results of the study showed that parents could not distinguish between ECE and Kindergarten. Kindergarten in not part of ECE and so that in learning process, parents emphasis on academic achievement without providing the the character building. Parents only focus on on reading and writing without paying attention to aspects of moral and religious values, physical, motor, social, emotional. In the aspect of the role of involvement, it shows the lack of role as parents of students to be involved in the implementation of early childhood education including parenting program activities, volunteers, communication, collaboration and learning at home. Lack of understanding of coastal parents in Buton Islands towards the implementation of early childhood education, it is necessary for schools to involve families in educational programs in order to gain enlightenment and knowledge about early childhood education.